KAFTEN: Productive Waqf Asset Development Applications to Support The Welfare of Islamic Boarding School - Ega Rusanti (Universitas Darussalam Gontor, 2021)
Waqf is a legal act of endowment to save and give a part of his property to be used for religious purposes and public welfare by the Syariah. One form of waqf management is establishing the Darul Istiqomah Islamic boarding school in Sinjai Regency, a waqf land area of 50.000 m2. But the form of empowerment is still not optimal due to lack of human resources and unclear direction developing productive waqf sustainability. The purpose of this study is to provide several choices of planning solutions in the form of KAFTEN application (Waqf for Islamic Boarding School), which synergizes related parties in maximizing the potential of waqf. This research is a qualitative descriptive and SWOT analysis using data collection techniques, namely direct interviews with the Darul Istiqomah Islamic Boarding School managers and students. Planning a solution offered by researchers to overcome the problems faced by waqf managers is to develop KAFTEN applications online, and offline that can be a means of education and mediation to synergize parties concerned with developing the potential for waqf and welfare of Islamic boarding schools. The implication of this research is to make KAFTEN a media for optimizing waqf in a directed and sustainable way.